2022
DOI: 10.1007/s12403-022-00513-0
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Simulations and Functional Cell Studies Evidence Similar Potency and Distinct Binding of Pacific and Caribbean Ciguatoxins

Abstract: Ciguatoxins (CTX) cause ciguatera poisoning, which is the most common reported human food poisoning related to natural marine toxins. Pacific ciguatoxins are the most abundant and studied CTX analogues; however, the growing distribution of Caribbean analogues and the limited data available on their biological effects make necessary to re-evaluate their relative potency. For decades, the guidelines established by regulatory agencies have assumed that the potency of the Caribbean CTXs were tenfold lower than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 63 publications
3
10
0
Order By: Relevance
“…The effects of increasing CTX3C concentrations, between 0.000001 and 10 nM, on the maximum peak inward sodium currents ( I Na ) and the activation voltage of human VGSC after single cell exposure were first evaluated and reported by our group . As previously reported, ,, CTX3C elicited a concentration-dependent decrease in the maximum peak amplitude of sodium currents being detected even at the lowest concentrations. In control conditions, the peak sodium current at −10 mV was −1156 ± 189 pA ( n = 13) decreasing in a concentration-dependent manner up to −692 ± 372 pA ( n = 3) after bath application of 1 nM CTX3C.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…The effects of increasing CTX3C concentrations, between 0.000001 and 10 nM, on the maximum peak inward sodium currents ( I Na ) and the activation voltage of human VGSC after single cell exposure were first evaluated and reported by our group . As previously reported, ,, CTX3C elicited a concentration-dependent decrease in the maximum peak amplitude of sodium currents being detected even at the lowest concentrations. In control conditions, the peak sodium current at −10 mV was −1156 ± 189 pA ( n = 13) decreasing in a concentration-dependent manner up to −692 ± 372 pA ( n = 3) after bath application of 1 nM CTX3C.…”
Section: Resultsmentioning
confidence: 91%
“…CTXs and BTXs bind to a common site of the sodium channel located at the cleft created by segment S5 of domain IV, segment S6 of domain I, and the P-loop (P1) that connects segments S5 and S6 of domain IV of the VGSC α-subunit , but with different affinities. Previous studies indicated that CTXs interact specifically and with higher affinity with sodium channels; , however, the differences in the chemical structures between the CTX analogues generate modifications in their binding and activity over VGSC. , BTXs are also considered to have a high binding affinity to sodium channels; , however, the differences between both groups of toxins are significant since studies of their binding affinity to rat brain sodium channels allowed to calculate an inhibitory constant (ki) of 0.041 nM for ciguatoxin-1B which was more than 50-fold higher than that of BTX-1 (2.24 nM) .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations